The role of general practitioners in Reunion in detecting alcohol use in pregnant women and identifying fetal alcohol spectrum disorder: a qualitative study - Sébastien Leruste; Louise Delfarguiel; Bérénice Doray; Coralie Loubaresse; Laetitia Sennsfelder; Thierry Maillard; Catherine Marimoutou; Michel Spodenkiewicz (BMC, 2023)
Abstract Background Fetal Alcohol Spectrum Disorder (FASD) is the leading cause of non-genetic intellectual disability and social maladjustment in children. International guidelines recommend abstinence from alcohol during pregnancy. Réunion is the most affected of all French regions with an estimated Fetal Alcohol Spectrum (FAS) prevalence of 1.2‰ births. General practitioners (GPs) are at the forefront of identifying patients with FASD. Objective: To understand how GPs identify FASD. Methods Qualitative study using a grounded theory approach, through semi-structured face-to-face interviews with GPs. Interviews were conducted with the aim of reaching theoretical saturation. These were transcribed verbatim and then analyzed by four researchers to ensure triangulation of the data. Results GPs reported barriers to the identification of FASD: challenges in overcoming social taboos and paradoxical injunctions, the influence of limited knowledge and experience, non-specific and highly variable symptoms, ambiguous classification and method of diagnosis involving the mobilization of a multidisciplinary team and lengthy consultations. Conversely, they felt competent to identify neurodevelopmental disorders of any cause, but were concerned about the long waiting time to access specialized care. From the perspective of GPs, it is crucial to prioritize promotion and training aimed at improving the identification and coordination of care pathways for children diagnosed with neurodevelopmental disorders, such as FASD.